2021
DOI: 10.3892/ijfn.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant properties of herb decoction extracts derived from Epirus, Greece

Abstract: For thousands of years, medicinal herbs have been an integral part of traditional medicine, since a number of them exhibit potent antioxidant properties, mainly associated with their rich content in bioactive compounds. Based on these attributes, nowadays, medicinal herbs are used for industrial purposes (e.g., as natural food additives) and are also evaluated as chemopreventive strategies for diseases associated with the disruption of redox homeostasis. In that frame, the aim of the present study was to appra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Geyikoglu et al ( 40 ) demonstrated that boric acid decreased the 8-OHdG expression level in ischemia reperfusion injury by acting as an antioxidant, anti-inflammatory and antiapoptotic agent. The results of TAC, TOS and LDH assays supported the results from the 8-OHdG staining assay ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 73%
“…Geyikoglu et al ( 40 ) demonstrated that boric acid decreased the 8-OHdG expression level in ischemia reperfusion injury by acting as an antioxidant, anti-inflammatory and antiapoptotic agent. The results of TAC, TOS and LDH assays supported the results from the 8-OHdG staining assay ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 73%
“…Cell-free methods are reliable as a preliminary screening of the effectiveness of the tested samples; therefore, further investigations using cell lines may provide information regarding the bioavailability, the metabolism and the uptake of the antioxidants constituents of the honey ( 69 ). The use of cell-based methods can also be used to examine the potential toxic or protective mechanisms ( 48 ). In the present study, a liver cancer cell line (HepG2) was used for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…GSH is the most abundant endogenous antioxidant, playing crucial roles in the detoxification and metabolic processes ( 71 ). GSH has the ability to donate a hydrogen atom from its sulfhydryl group, thus scavenging the free radicals and other electrophiles either directly or indirectly used as a substrate by antioxidant enzymes ( 48 , 72 ). In the present study, the honey samples did not induce the production of GSH in HepG2 cells, apart from the oak honey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, evidence in the literature has also widely debated the chemo-preventive, immunoregulatory, antioxidant and antiatherogenic properties of honey (58)(59)(60)(61). Nevertheless, information regarding the properties of Greek honey in literature and notably from in vivo studies are scarce even though Greece is part of the eastern Mediterranean, creating a rich and diversified flora habitat (62,63). This rich flora biodiversity combined with the overflowing sunshine, creates an ideal environment resulting in a variety of honey types originating from pine, thyme, fir and other conifers (64,65).…”
Section: Discussionmentioning
confidence: 99%